PENERAPAN SISTEM ABSENSI ONLINE BERBASIS IOT (INTERNET OF THINGS) MENGGUNAKAN MIKROKONTROLER NODEMCU ESP8266 DENGAN ALAT DUKUNG SCAN RFID KARTU PELAJAR - Haris Priazun; Ade Sumaedi (Infotech: Journal of Technology Information, 2025)
Measuring student discipline can be done by recording their attendance. Attendance is crucial evidence of participation in every institutional reporting activity. In education, attendance is used to record who is present in class. However, traditional attendance systems that call students' names one by one face various challenges, such as taking a long time to record data, the potential for damage to attendance records, and lack of accuracy. This research focuses on implementing an online attendance system based on the Internet of Things by utilizing the ESP8266 microcontroller and RFID student card scanner at SMP Negeri 1 Carenang. This system is designed to address the limitations of manual attendance systems that are inefficient and prone to errors. By using the ESP8266 microcontroller as the data processing center, the RFID MFRC522 sensor to read student identity cards, and the MySQL database to store attendance data, this system allows real-time monitoring of student attendance through a website accessible to teachers and parents. The implementation of this IoT based online attendance system is expected to improve student discipline and motivation, as well as facilitate teachers in accurately and effectively monitoring student attendance.